Interaction between Gender and Cognitive Factor toward Investment Decision - Tiar Lina Situngkir; Nugraha Nugraha; Disman Disman; Yayat Supriyatna (University of Merdeka Malang, 2022)
This study aims to analyze whether there is an influence of irrational behaviour of individual investors in determining investment decisions. The irrational behaviour studied in this article are overconfidence and risk aversion. To increase the complexity, the moderating variables of gender and income level are used to sharpen the influence on investment decisions. The data used are primary data collected from 161 individual investor respondents. The data available in this study were analysed using the Moderated Regression Analysis Technique. From the data processing results, it was found that irrational behaviour proxied by overconfidence and risk aversion has an influence on investors in determining investment decisions. It is proven that risk aversion interacts with gender in influencing investment decisions. At the same time, gender does not interact with the independent variable in influencing investment decisions. JEL : G4, G41